Pengaruh Kesadaran Wajib Pajak dan Kualitas Pelayanan Pajak terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor pada Kantor Samsat Kabupaten Garut - lina nurlaela (Fakultas Ekonomi Universitas Garut, 2018)
The purpose of this study is to determine the awareness of taxpayers, quality of tax services and taxpayer compliance and to examine the effect of taxpayer awareness and quality of tax services on motor vehicle taxpayer compliance at the SAMSAT Office of Garut Regency. The method used in this research is descriptive method. The data collection technique uses library research and field research by means of interviews and distributing questionnaires in the form of questionnaires distributed to respondents, namely motor vehicle taxpayers. The type of data used is quantitative data, with primary data sources. The data processing technique uses multiple linear regression analysis with a significant level of research results (error value) of 5%. Based on the results of the study partially shows that taxpayer awareness affects taxpayer compliance, and the quality of tax services. While the results of the research simultaneously show that taxpayer awareness and quality of tax services have an effect on motor vehicle taxpayer compliance.